Risks of Corporate Entrepreneurship: Autonomy and Agency Issues - Shimizu, Katsuhiko (Katsu) (Organization Science, 2012)
Although research on corporate entrepreneurship (CE) has attracted increasing attention, risks of CE are not well examined. In this paper, we examine direct and indirect agency risks associated with providing middle and operational managers with autonomy in the hopes of encouraging CE. The key ideas behind our discussion involve two dilemmas of CE. (1) To solve the risk-averseness problem of middle and operational managers and unleash their entrepreneurial ideas, top management needs to encourage autonomous behaviors, which can also exacerbate a different type of agency problem: opportunistic behaviors. (2) Although the generation of new ideas to explore new strategic directions and/or opportunities is important, the very newness of the ideas make them difficult to evaluate, and thus the selection process may be perceived as unfair by some managers. We propose that (a) stock options, (b) passive monitoring, and (c) perceived procedural justice would attenuate the negative side effects associated with CE, such as opportunistic behaviors and perceived unfairness. Although research in CE often stresses autonomy of middle and operational managers for new idea generation as important, examining the whole process in terms of idea generation, selection, and implementation with respect to potential risks will extend the CE literature.